Pengenalan Fauna Penghuni Ekosistem Mangrove Bagi Anak-Anak Usia Sekolah di Kampung Kondo, Distrik Naukenjerai - Merly, Sendy Lely; Untari, Untari; Tuhumena, Jeremias; Redu, Silas Tanggu; Ismanto, Heru (Jurnal Pengabdian Masyarakat (ABDIRA), 2024)
The mangrove forest ecosystem is an important ecosystem in coastal areas. It functions as a greenbelt and is able to provide a source of food for people living in coastal areas. Even the mangrove ecosystem is a habitat for various fauna that inhabit the ground floor, trees, and also the waters in this ecosystem. The role of early childhood is very important, by providing a proper understanding of both the types of fauna that inhabit the mangrove ecosystem on the coast of Kampung Kondo and what are the benefits of each fauna, children will be able to recognize the potential they have, utilize and manage the resources they have based on local wisdom they have. The method used is the exploring method where together with the children enter the mangrove forest area and the samples found are immediately identified and, together they pay attention to the habitat of the fauna found. The results of this activity are that children are able to identify 5 gastropods species, 1 shellfish species, 2 crab species, and 1 fish species, and ultimately, understand the habitat of each fauna.